EXPRESSION OF FOUR CYTOKINE/CHEMOKINE GENES IN PERIPHERAL BLOOD MONONUCLEAR CELLS INFECTED WITH DENGUE VIRUS - Sri Masyeni, Dewa Ayu Putri; Hadi, Usman; Kuntaman, Kuntaman; Yohan, Benediktus; Margyaningsih, Nur Ita; Sasmono, R Tedjo (Indonesian Journal of Tropical and Infectious Disease, 2019)
Overproduction of numerous pro-inflammatory cytokines, during dengue virus (DENV) infection, has been related to plasma leakage in the vascular endothelium and studied elsewhere with conflicting results. The current study objective is to evaluate the expression of four cytokine/chemokine genes following DENV-2 infection within peripheral blood mononuclear cells (PBMC) isolated from a healthy donor. Venous blood was drawn,  and PBMCs were isolated using Ficoll density gradient centrifugation. Cells were maintained in culture medium and infected with Indonesian isolate of DENV-2. Cells were harvested and followed by total RNA extraction and reverse-transcription into cDNA using oligo d(T) primers and Reverse Transcriptase enzyme system. The SYBR Green-based quantitative qRT-PCR was used to calculate the relative expression of IL-6, IL-8, IP-10 and MIP-1β- encoding genes during infection time points, compared to uninfected cell controls. The observation of the cytokine was on the 6 and 18 hours post-infection. The different expression profiles of cytokines/chemokines were observed. The up-regulation of gene expression was observed for IL-8 and IP-10. In contrast, the down-regulatory of IL-6 and MIP-1β genes expression was documented during the infection period. The cytokine IL-8 and IP-10 are potent chemoattractants  in the recruitment  of neutrophil, basophil, and lymphocytes in response to an infection. The highlight of this study is on the up-regulation of IL-8 and IP-10 genes expression which may confirm the roles of these chemokines in the pathogenesis of dengue infection.